Generators and relations for the semigroups of increasing functions on N and Z - Doroshenko, V. (Algebra and Discrete Mathematics, 2005)
The semigroups of all increasing functions over N
and Z are considered. It is shown that both these semigroups do
not admit an irreducible system of generators. In their subsemigroups of cofinite functions all irreducible systems of generators are
described. The last semigroups are presented in terms of generators
and relations.